2017
DOI: 10.14245/kjs.2017.14.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Histiocytosis of the Thoracic Spine in an Adult

Abstract: We report a case of a 45-year-old man with a complaint of both leg weakness and hypoesthesia. Radiological evaluation revealed an osteolytic lesion of the ninth thoracic vertebra. The patient underwent posterior corpectomy with total excision of the tumor, mesh cage insertion with posterior screw fixation and subsequent radiotherapy. Histology confirmed the diagnosis of Langerhans cell histiocytosis (LCH). This case report presents the diagnostic work-up, histopathological evaluation, and the treatment procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Kim et al [ 11 ] in 2017, have also reported a case of LCH in the thoracic spine of an adult 45-year-old man who presented with motor and sensory deficits of the lower extremities [ 11 ]. His thoracic spine imaging revealed an osteolytic lesion of the eighth and ninth thoracic vertebra causing pathological fracture along with myelopathy from T8 to T10 and cord compression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kim et al [ 11 ] in 2017, have also reported a case of LCH in the thoracic spine of an adult 45-year-old man who presented with motor and sensory deficits of the lower extremities [ 11 ]. His thoracic spine imaging revealed an osteolytic lesion of the eighth and ninth thoracic vertebra causing pathological fracture along with myelopathy from T8 to T10 and cord compression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…He was surgically treated with posterior corpectomy and total tumour excision. A mesh cage was inserted, and posterior screw fixation was performed [ 11 ]. Following surgery, the patient underwent radiotherapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations